The Position of the Letter from the Chief of the Supreme Court and the Decision of the Constitutional Court in the Polemic on the Advocate's Oath - Wahab, Mirnawanti; Bachmid, Fahri (Journal of Law, Politic and Humanities, 2024)
To carry out the profession of an advocate, a person must go through various stages regulated in the Law on advocates, including the process of education and appointment through oaths. However, the publication of the Letter of the Chief Justice of the Supreme Court of the Republic of Indonesia regarding the oath of advocates has created a polemic among law enforcement. This study aims to examine two main issues: first, the substance and position of the Letter of the Chief Justice of the Supreme Court of the Republic of Indonesia regarding advocate oaths; and second, the substance and position of the Advocate Organization's Constitutional Court Decision. As doctrinal legal research, this study uses statutory and contextual approaches to secondary data in the form of primary and secondary legal materials. The results of the analysis conclude that the Letter of Chief Justice of the Supreme Court is recognized as a product of laws and regulations in Indonesia, so it must comply with the principles regarding statutory regulations. However, it is considered that this policy cannot become a binding legal product because it is considered contradictory to the law on advocacy organizations. This was justified by the Constitutional Court's decision, which considered that there was an error in the substance of the letter. The Court, in its legal considerations, then determined the Indonesian Advocates Association (PERADI) as the only advocate organization that was given eight authorities, including carrying out Advocate Profession Special Education (PKPA), Advocate Professional Examination, and carrying out the oath of attorney candidates